Classification of the homonyms in Japanese - Rahman А (Journal of Oriental Studies, 2016)
In this paper we will deal the classification of homonyms in Japanese. The article presents 5 classification parameters homonyms in Japanese. We combined homonyms in groups according to these parameters. Also giving examples of these groupings that is being used in modern language.